REDUCTION OF MORTALITY RATE ON TROPICAL FISH FOR EXPORT USING ARTIFICIAL WETLANDS ON THE EFLUENT WATERS IN THE LORETO REGION – PERU - YALÁN VILLAFANA, Raúl Javier (2018)
In Acuatrade SAC, tropical fish export company in the Loreto Region, the mortality rate was up to 12%, it was detected that such loses were due to the un constant water quality, this is well water and is treated every day with flocculation immediately after be extracted. The use of artificial wetlands for reuse and recycling of the effluent waters from the tropical fish facility reduced drastically the mortality rate and the use of well water